(untitled) (Journal of Economics and Management Research, 2021)
هدفت هذه الدراسة إلى تسليط الضوء على الإمكانات الاقتصادية والاجتماعية للاقتصاد البنفسجي التي يمكن أن تخدم التنمية المستدامة مع التعرض إلى تجارب دول منظمة التعاون الاقتصادي والتنمية باعتبارها رائدة الاقتصاد البنفسجي في العالم لاستخلاص دروس يمكن الاستفادة منها في بناء إستراتيجية وطنية تعزز مكانة الاقتصاد البنفسجي. خلصت الدراسة إلى أن الاقتصاد البنفسجي، بفضل الصناعات الثقافية والإبداعية، يمتلك من الإمكانيات ما يمكنها من تعزيز التنمية المستدامة، وهو ما دفع دول منظمة التعاون الاقتصادي والتنمية إلى تشجيع نمو الصناعات الثقافية والإبداعية. Abstract: The present study shed light on the economic and social potentials of the purple economy that can serve sustainable development, with exposure to the OECD countries’ experiences as they are the global pioneers of the purple economy, to extract lessons that can be used in building a national strategy to enhance the purple economy. The study concluded that the purple economy, thanks to the cultural and creative industries, has the potential to promote sustainable development, which prompted OECD countries to encourage the growth of cultural and creative industries.